A pesquisa na pós graduação: balanço da produção discente sobre criança/infância (PUC-SP - 1978/2004) - Guimarães, Renata de Castro (2007)
This work was accomplished between 2005 and 2007. The aim of this work was to analyze what students have been writing about children, in a way to understand how the child has been built as a research object. An exhausting survey of master s degree dissertations and doctor theses defended in some Post Graduation Courses at Pontifícia Universidade Católica de São Paulo (PUC-SP) from 1978 to 2004 was held. The key words used for this research were: child , children , childhood . The selection of works was done based on their abstracts. This investigation was limited to theses and dissertations from the following programs: Education: History, Politics, Society; Education: Curriculum; Education: Psychology of Education; Clinical Psychology; Social Psychology; Social Sciences, and Social Service. The procedures for classifying contents, according to Bardin (1995), were used as a reference for the pre-analysis of the documents. The work has two parts: a global and quantitative analysis embracing data from all 144 productions involving program, year of defense, tutors, general theme and specific theme; and an exhausting quantitative and qualitative analysis of 23 woks focusing the child. The quantitative part involved the following indicators: year of defense, program, tutors, general theme(s), theme(s) basis, main results and conclusions. The qualitative part took a detailed analysis of the works, focusing what each of them had created specifically concerning the child. We could certify that the analyzed researches build the child under the psychological contributions and express four tendencies: the child as a developing being, the child as subject of social relations through interactions, the consequences for children with both organic and psychic alterations and the child as a member of the scholar institution as a student